The agricultural situation in Western Europe : review of 1970 and Outlook for 1971 - United States. Dept. of Agriculture, Economic Research Service (Washington, D.C. : Dept. of Agriculture, Economic Research Service, 1971)
Agricultural performance in the Communist Countries was generally favourable in 1971. In the USSR and Mainland China, production remained at the high level of 1970. A small decline in Soviet crop production was offset by an increase in livestock output. Also, livestock gained in Mainland China while the grain harvest was lower. East European Agriculture, however, recovered sharply in 1971 after suffering from flood damage and winterkill in 1970.
lje 06/07/2017
Loans
Keywords: Agriculture---Economic aspects; Agricultural Development; Western Europe